DEVELOPING ENGLISH LEARNING MATERIALS INTEGRATED WITH CHARACTER VALUES FOR THE ELEMENTARY SCHOOL STUDENTS - Rita Pusparini; Suwarsih Madya (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2016)
Developing English Learning Materials Integrated with Character Values for the Elementary School Students. The aim of this research study is to develop English learning materials integrated with character values for the elementary school students. This research is a research and development study. The development of these product was carried out in three phases, i.e.: (1) planning, involving conducting need analysis and studying of literature; (2) developing the product, involving developing the course grid and developing the first draft of the product; (3) evaluating the product, involving expert validation, preliminary try-out, and main try-out. The result of this study shows that(1) the quality of the product, in terms the content, is in the very good category with the average score of 4.49 and 4 for the integrated character values, which means the quality is in the good category; (2) the quality of the product in terms’ media is in the good category, with the average score of 4; (3) the students’ responses toward the task and the aspect contributing the product at the preliminary try-out, the first validation, and the second validation showed 3.60 and 3.55, 3.47 and 3,54, and 3.40 and 3.43 for the mean score, all of which are in the very good category; (4) the teacher’s responses toward the Student Book and Workbook at the preliminary try-out, the first validation, and the second validation showed 3.24 and 3.13, 3.29 and 3.18, and 3.29 and 3.18 for the mean scores, all of which are in the very good category. This means the set of English learning materials is effective and appropriate to be used in the teaching and learning process for the elementary school students